2007
DOI: 10.1111/j.1745-7254.2007.00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of silybin on biophysical properties of phospholipid bilayers

Abstract: Aim: Silybin (silibinin) is major biologically active flavonolignan extracted from milk thistle (Sylibum marianum). Its biological activities include hepato‐protection, anticancer properties, and antioxidant‐ and membrane‐stabilizing functions. Although membranes are postulated to be one of the cellular targets for silybin, little is known about its interaction with phospholipid bilayers. Methods: In the present work, the interactions of silybin with phosphatidylcholine bilayers were studied in detail using fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…This feature enables silybin penetration mainly to lipid bilayer component of the membrane leading to strengthen its biophysical structure. These effects on membrane stabilization may correspond to the cell protection and lack of serious side effects after the drug administration [38]. …”
Section: Discussionmentioning
confidence: 99%
“…This feature enables silybin penetration mainly to lipid bilayer component of the membrane leading to strengthen its biophysical structure. These effects on membrane stabilization may correspond to the cell protection and lack of serious side effects after the drug administration [38]. …”
Section: Discussionmentioning
confidence: 99%
“…Various studies indicated that silibinin significantly increases glutathione levels, which serve as a free radical scavenger (Das and Vasudevan, 2006). Silibinin is relatively hydrophobic and its penetration into the cell is limited (Sainz-Pardo et al, 1994) and membrane structures are postulated to be one of the cellular targets for silibinin as it interacts with the surface of lipid bilayer (Wesolowska et al, 2007), its effect on erythrocytes may be explained by their incorporation into these lipid bilayers of the cell membrane leading to reducing hemolysis. Silibinin on the other hand, is able to increase the activity of both superoxide dismutase and glutathione peroxidase, which may explain the protective effect of the drug against free radicals and also stabilizing the effect on the red cell membrane (Altorjay et al, 1992).…”
Section: Controlmentioning
confidence: 99%
“…Such behavior of silybin in membranes is in line with its postulated biological functions. Membrane stabilization and cell protection may correspond to the observed lack of serious side effects of this drug (Wesołowska et al 2007). Silybin at concentrations higher than 50 μM decreased LDH activity and total cellular protein content.…”
Section: Discussionmentioning
confidence: 99%